The legend of Sleepy Hollow - Irving, Washington, 1783-1859.; Kelly, Jack. (New York : Baronet Books, 1995)
A superstitious schoolmaster, in love with a wealthy farmer's daughter, has a terrifying encounter with a headless horseman.
Keywords: Ghosts -- Fiction; New York (State) -- Fiction